Comparison of microbially induced sedimentary structures in the Palaeoproterozoic Magaliesberg (Transvaal Supergroup) and Makgabeng (Waterberg Group) Formations, Kaapvaal craton, South Africa - Eriksson, Patrick George (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.